ANTERIOR ARCH CROWDING -A POSSIBLE PREDICTOR FOR MANDIBULAR THIRD MOLAR IMPACTION - Lakhani, M Junaid; Kadri, Wahab; Mehdi, Hassan; Sukhia, Houshang; Bano, Asma; Yaqoob, Sania (Journal of Ayub Medical College Abbottabad, 2011)
Background: Impaction of the 3rd molar is a high incident problem occurring in up to 73% of young adults in Europe. Appropriate follow-up routines and optimal timing for surgical removal of the 3rd molars can be established in patients judged to be at increased risk of impaction. The purpose of this study was to identify risk factors for mandibular 3rd molar impaction in adolescent orthodontic patients and to establish anterior arch crowding as a predictive model for mandibular 3rd molar impaction. Methods: Pre-treatment Orthopantomogram (OPG) of 158 orthodontic patients with the evidence of anterior arch crowding on pre-treatment study models were evaluated for mandibular third molar position. Results: Out of 158 patients, 45 were male and 113 were female. Ninety-seven (61%) of the patients showed anterior arch crowding with a space discrepancy of 5-10 mm calculated on the pretreatment study models. Fifty-seven patients showed 107 third molar impactions. Anterior arch crowding in these patients was ranging from 7-10 mm. Out of 107 impacted third molars 73 were Mesioangular 14 were Distoangular 6 were Vertical and 14 were Horizontal. Conclusion: If the arch size is smaller as compared to the tooth size the evidence of lack of space would be there in anterior segment as crowding and in posterior segment as 3rd molar impaction. Keywords: Mandibular third molar impaction; anterior arch crowding